2009
DOI: 10.1017/s1041610209991189
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of health behavioral risks and cognitive health in older adults

Abstract: The review demonstrates accumulating evidence supporting health behavioral effects in reducing the risk of cognitive decline and dementia. Results indicate potential benefits of healthy lifestyles in protecting cognitive health in later life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
156
3
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(171 citation statements)
references
References 57 publications
7
156
3
5
Order By: Relevance
“…Cognitive health can be considered as a continuum of cognitive function ranging from optimal to decline to impairment and dementia [12,18]. It was cautiously concluded from a meta-analysis of 23 studies that there was some evidence to suggest that alcohol consumption in earlier adult life may be protective against incident dementia later [19].…”
Section: Systematic Reviews and Meta-analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Cognitive health can be considered as a continuum of cognitive function ranging from optimal to decline to impairment and dementia [12,18]. It was cautiously concluded from a meta-analysis of 23 studies that there was some evidence to suggest that alcohol consumption in earlier adult life may be protective against incident dementia later [19].…”
Section: Systematic Reviews and Meta-analysesmentioning
confidence: 99%
“…Clustering of multiple risk factors increases the risk of dementia [76]. Conversely a reduction or removal of these risk factors reduces the risk, or delays the onset, of cognitive decline and dementias [12], indicating the advantages of adopting a healthy diet and lifestyle that includes moderate alcohol consumption.…”
Section: Alcohol Consumption In Younger and Middle Aged Adults And Efmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence on modifiable risk factors of cognitive decline indicates the potential benefit of physical activity on maintaining cognitive function in late life (Lee et al 2010b;Plassman et al 2010). Populationbased studies of older adults have reported a slower rate of decline in cognitive function among those engaged in higher levels of physical activity at baseline (Ku et al 2012;Lytle et al 2004;Weuve et al 2004;Yaffe et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…A study by Lee et al (2010) cites some environmental factors related to lifestyle in increased or decreased risk of developing Alzheimer's disease. Among the modifiable risk factors, evidence suggests that certain behaviors such as smoking, physical activity, alcohol intake, diet and body weight significantly influence cognitive function and dementia in advanced age (ANSTEY et al, 2007;GOROSPE;DAVE, 2007;BEYDOUN et al, 2008;PETERS et al, 2008).…”
Section: Sgarbieri V C; Pacheco M T Bmentioning
confidence: 99%